Secretory phospholipase A2 in SARS-CoV-2 infection and multisystem inflammatory syndrome in children (MIS-C). Issue 23 (December 2021) - Kuypers, Frans A; Rostad, Christina A; Anderson, Evan J; Chahroudi, Ann; Jaggi, Preeti; Wrammert, Jens; Mantus, Grace; Basu, Rajit; Harris, Frank; Hanberry, Bradley; Camacho-Gonzalez, Andres; Manoranjithan, Shaminy; et al.
Secretory phospholipase 2 (sPLA2) acts as a mediator between proximal and distal events of the inflammatory cascade. Its role in SARS-CoV-2 infection is unknown, but could contribute to COVID-19 inflammasome activation and cellular damage. We present the first report of plasma sPLA2 levels in adults and children with COVID-19 compared with controls. Currently asymptomatic adults with a history of recent COVID-19 infection (≥4 weeks before) identified by SARS-CoV-2 IgG antibodies had sPLA2 levels similar to those who were seronegative (9 ± 6 vs.17 ± 28 ng/mL, P = 0.26). In contrast, children hospitalized with severe COVID-19 had significantly elevated sPLA2 compared with those with mild or asymptomatic SARS-CoV-2 infection (269 ± 137 vs. 2 ± 3 ng/mL, P = 0.01). Among children hospitalized with multisystem inflammatory syndrome in children (MIS-C), all had severe disease requiring pediatric intensive care unit (PICU) admission. sPLA2 levels were significantly higher in those with acute illness <10 days versus convalescent disease ≥10 days (540 ± 510 vs. 2 ± 1, P = 0.04). Thus, sPLA2 levels correlated with COVID-19 severity and acute MIS-C in children, implicating a role in inflammasome activation and disease pathogenesis. sPLA2 may be a useful biomarker to stratify risk and guide patient management for children with acute COVID-19 and MIS-C. Therapeutic compounds targeting sPLA2 and inflammasome activation warrant consideration.